2022
DOI: 10.1038/s42003-022-03994-6
|View full text |Cite
|
Sign up to set email alerts
|

SMAD2/3 mediate oncogenic effects of TGF-β in the absence of SMAD4

Abstract: TGF-β signaling is involved in pancreatic ductal adenocarcinoma (PDAC) tumorigenesis, representing one of the four major pathways genetically altered in 100% of PDAC cases. TGF-β exerts complex and pleiotropic effects in cancers, notably via the activation of SMAD pathways, predominantly SMAD2/3/4. Though SMAD2 and 3 are rarely mutated in cancers, SMAD4 is lost in about 50% of PDAC, and the role of SMAD2/3 in a SMAD4-null context remains understudied. We herein provide evidence of a SMAD2/3 oncogenic effect in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 73 publications
(74 reference statements)
1
6
0
Order By: Relevance
“…The initiation of TGF-β's signal transduction transpires through serine or threonine receptor kinases (Zhang et al, 2014). This leads to the phosphorylation of intracellular transducers Smad2/3, which subsequently form a complex with Smad4 (Bertrand-Chapel et al, 2022). This intricate assemblage traverses from the cell membrane into the nucleus, thereby eliciting a transcriptional response to TGF-β within the nucleus.…”
Section: Discussionmentioning
confidence: 99%
“…The initiation of TGF-β's signal transduction transpires through serine or threonine receptor kinases (Zhang et al, 2014). This leads to the phosphorylation of intracellular transducers Smad2/3, which subsequently form a complex with Smad4 (Bertrand-Chapel et al, 2022). This intricate assemblage traverses from the cell membrane into the nucleus, thereby eliciting a transcriptional response to TGF-β within the nucleus.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, it was shown that the depletion of CDCA5 resultedin a downregulation of the phosphorylation of Smad2/3. A study observed that the oncogenic effects of TGF-β can be mediated by Smad2/3 even when Smad4 is absent [ 31 ]. Unfortunately, the current study failed to elucidate the specific molecular mechanism, which will be the direction of thefuture research endeavors.…”
Section: Discussionmentioning
confidence: 99%
“…SMAD4 has been suggested as a central component of EMT transition in human colorectal cancer ( 45 ), but in absence of SMAD4, alternative factors may take over the gene regulatory functions of SMAD4 to drive EMT ( 46 ). In this vein, it has been shown that in a SMAD4-null context, SMAD2 and SMAD3 transduce TGFβ-driven cell migratory and invasive properties via the initiation of a SMAD4-independent “collective migration” transcriptional program ( 47 ). Dynamic assembly of cytoskeletal structures on the leading edge of motile cells requires precise spatial and temporal control of protein trafficking.…”
Section: Discussionmentioning
confidence: 99%